Cod, Herring and Sprat. Issue 2 (September 2016) - Quaas, Martin F.
Abstract: Joining forces, not fragmentation: a wide range of research areas can contribute to sustainable fisheries, from marine biology to economics and law. The Cluster of Excellence "The Future Ocean" is seeking to establish a dialogue.